2011
DOI: 10.1080/09593969.2010.481090
|View full text |Cite
|
Sign up to set email alerts
|

Italian coalitions and electoral promises: assessing the democratic performance of the Prodi I and Berlusconi II governments

Abstract: Italian party coalitions (from both the centre-left and the centre-right) have enacted an average of 57% of the pledges included in their common manifestos. In relative terms, Italian political parties keep their electoral promises much less than parties governing in single-party government, but slightly outperform those that form post-electoral coalitions. Although this finding contradicts the widespread pessimism about Italy's performance, it also illustrates that there is no significant advantage to bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…10 One of the most evident novelties of the Second Republic was the bipolar nature of party competition, which took place between two coalitions: one of the centre right, the other of the centre left. 11 Coalitions were now assembled before elections (Golder 2006) and stipulated pre-electoral coalition agreements (Moury and Timmermans 2008;Moury 2010Moury , 2011. In contrast to the situation during the First Republic, all parties represented in Parliament were parties enjoying coalition potential (Sartori 2005).…”
Section: The Theoretical Premisementioning
confidence: 97%
“…10 One of the most evident novelties of the Second Republic was the bipolar nature of party competition, which took place between two coalitions: one of the centre right, the other of the centre left. 11 Coalitions were now assembled before elections (Golder 2006) and stipulated pre-electoral coalition agreements (Moury and Timmermans 2008;Moury 2010Moury , 2011. In contrast to the situation during the First Republic, all parties represented in Parliament were parties enjoying coalition potential (Sartori 2005).…”
Section: The Theoretical Premisementioning
confidence: 97%
“…To answer this general question one could have profited from two elements that are missing here. First the comparative evidence available on the fulfilment of election pledges would have put these data in a different perspective (Moury, 2011 has shown that Italian governments of both coalitions to be near the bottom in the ranking of promises fulfilled by governments in Europe). Second, the use of data on voting motivations from the national election studies (in Italy, Itanes, and in Switzerland, the Fors survey) would have shown the motivations of the voters rather than those of the 'insiders'.…”
mentioning
confidence: 98%
“…Recent pledge research (Kostadinova, 2013;Toros, 2015;Praprotnik, 2015;Thomson et al, 2014;Naurin, 2013;Dobos and Gyulai, 2015) mostly takes inspiration from a small selection of classic pieces in pledge research (Royed, 1996;Artés, 2013;Artés and Bustos, 2008;Naurin, 2011;Moury, 2011;Mansergh and Thomson, 2007;Costello and Thomson, 2008; and the APSA papers by a group of first generational pledge scholars: Thomson et al, 2010; and the theoretical literature these classic pieces make reference to.…”
Section: Iv1 the Theoretical Sources Of Pledge Researchmentioning
confidence: 99%